The Numerical and Experimental Investigation of the Change of the Thermal Conductivity of Expanded Polystyrene at Different Temperatures and Densities - Battal Doğan; Hüsamettin Tan (International Journal of Polymer Science)
The determination of the thermal conductivity of insulation materials depending on which parameters in the application as well as the production is very important. In this direction, the parameters affecting thermal conductivity should be determined to improve the efficiency of the insulation materials. It is also a fact that expanded polystyrene blocks have different thermal conductivities at the same density value depending on the production process. In this study, it was determined, experimentally and numerically, that the thermal conductivity of expanded polystyrene material at different densities is dependent on which parameters and changes in temperature. Expanded polystyrene materials consist of blocks of 30×30 cm with density of 16, 21, and 25 kg/m3 and a thickness of 20 mm. Thermal conductivity measurements were performed in FOX 314 (Laser Comp., USA) operating in accordance with ISO 8301 and EN 12667 standards. The measurements were made for expanded polystyrene blocks at the average temperatures of 10°C, 20°C, 30°C, and 40°C. The numerical study has three stages as the acquisition of electron microscope images (SEM) of expanded polystyrene blocks, modeling of internal structure geometry with CAD program, and realization of solutions with a finite element-based ANSYS program. Findings from experimental and numerical studies and the parameters affecting thermal conductivity were determined. Finally, it is thought that numerical methods can be used to obtain a preliminary idea for EPS material in determining thermal conductivity by comparing the findings of experimental and numerical studies.